TÜRKİYE’DE YEREL YÖNETİM BAKANLIĞI DENEYİMİ VE GÜNÜMÜZDEKİ GEREKLİLİĞİNİN SORGULANMASI - (:unkn) unknown (My University, 2015)
Türkiye'de 1978 yılında kurulan ve idari sistem içerisinde kök salması beklenmeden 1979 yılında kapatılan Yerel Yönetim Bakanlığı'nın gerekliliği günümüzde büyükşehir belediyelerinin sayısının ve öneminin artmasına bağlı olarak tekrar sorgulanmaya başlanmıştır. Çalışmada 42. Türkiye Cumhuriyeti Hükümeti zamanında kurulan ve 22 ay sonra kapatılan Yerel Yönetim Bakanlığı'nın kurulmasını gerektiren nedenler, Bakanlığın var olduğu süre zarfında yaptığı faaliyetler ve kapatılma süreci değerlendirilmektedir. Yerel Yönetim Bakanlığı'nın hizmet verdiği süre zarfında devletin yerel yönetimler üzerindeki gözetim ve denetiminin azaltılmaya çalışıldığı ve belediyelerin gelirlerini arttırıcı girişimlerde bulunulduğu tespit edilmiştir. Yerel Yönetim Bakanlığı'nın kaldırılması ile beraber yerel yönetimlerle ilgili birçok görev, yetki ve sorumluluk geçmişte olduğu gibi yine 3152 sayılı İçişleri Bakanlığı'nın Teşkilat ve Görevleri Hakkında Kanun ile İçişleri Bakanlığına bağlı Mahalli İdareler Genel Müdürlüğü'ne devredilmiştir. Çalışmada ayrıca Norveç, İngiltere, İrlanda, Yeni Zelanda, Kuzey Kıbrıs Türk Cumhuriyeti (KKTC), Kosova, Uganda, Zambia ve Filistin Yerel Yönetim Bakanlığı uygulamaları örnek verilerek Türkiye'deki gerekliliğine vurgu yapılmak istenmiştir. Sayısı 2014 yılı itibariyle 30 olan büyükşehir belediyelerinin; gerek il mülki sınırında hizmet veriyor gerekse eskiye nazaran birçok hizmetle sorumlu olması dikkate alındığında yerel yönetimlerin idari sistemimiz içerisindeki öneminin ve işlerliğinin artacağı anlaşılmaktadır. Bu kapsamda çalışmada, önemi artan yerel yönetim birimlerini, merkezi yönetimle ilişkilendirecek ve yerel yönetimlere gerekli önemi verecek Yerel sorgulanmaktadır. Yönetim Bakanlığı'nın oluşturulmasının gerekliliği

Local governments have maintained their property especially as a part of political (within the frame of political will) will in the process. Organizational structures, duties, powers and responsibilities of local governments were determined by guardianship approach of central government. However, nowadays the decisiveness and conversion occur with the under-nation state or supra-national aprroach in the scope of globalization-localization. In this process, it is seen that the relationship between central and local government and guardianship auditing is generally carried out by a ministry. In Turkey, this ministry has been Ministry of Interior except a short period of time. However, when considering the political and international developments and changes in public administration paradigm, it is seen that the local authorities gained importance, the state took a regulatory role and conversion about indigenisation occurred. Necessity of Ministry of Local Government in Turkey, which was founded in 1978 and closed in 1979 without waiting to take root in administrative system, was examined depending on increasing number and importance of metropolitan municipality. Both metropolitan municipalities and small-scaled municipal organizations have tried to be managed for a long time by Municipality Law No. 1580 came into force in 1930. Even though necessary changes were made, the implementation of the same law for many small and large scaled municipalities both generalized and made different local problems. Thus, lots of service which local government could not offer until that day were provided in the 1950s by central government. After 1960s, many important projects and reports were prepared for solving the problems of public administration and local administration; however, these studies were not implemented due to political instability. During 1970s, many important studies were carried out in specific to local governments to solve the rapidly growing urban population and urban area problems on the basis of big city management. All these studies were made by the Ministry of Development and Housing and the Ministry of Interior. However, as a result of working like a security ministry in the political turmoil, it was impossible for the Ministry of Interior to solve the problems of local in this period. In the 1978 a different way was chosen to solve the local governments problems which did not support reports and systemic changes, but support a ministery which will do these changes. Thus the ministry of local government was founded at first in due time of the 42 th Government of Turkis Repuclic for the purpose of solving the local goverments' administrative and fiscal problems and bringing efficiency and functionality to these governances. In the first place, the bank of provinces from the Ministry of Development and Housing, general directorate of local administrations from the Ministry of Interior, Planning Departments of City and Local Governments from the state Türkiye’de Yerel Yönetim Bakanlığı Deneyimi ve Günümüzdeki Gerekliliğinin… 353 Turkish Studies International Periodical For the Languages, Literature and History of Turkish or Turkic Volume 10/1 Winter 2015 planning organization included within the ministry of the Local Government. Later, the General Directorate of Local Authorities, Special Provincial Administrations and General Directorate of Villages, General Directorate of Municipalities and the General Directorate of the FundLoans and the Tecnical Evaulation were organized in three different general directorate within the Ministry of the Local Governments. Also, General Directorate of Education was established within the Ministry of Local Governments. While the budget of the Ministry of Local Government was 505 million TL in the 1978, it was one billion 550 million TL in the 1979 and the Ministry has grown very fast in a short time. During the 22 months when the ministry worked, it aimed to make the local governments more flexible in terms of administrative and financial aspects. Also, many local government unions that are still active were established in this period. However, the Ministry of Local Governments were criticized because of the short time activities and it was qualified as "the Ministry of Municipality" due to being an organization which taking control on the municipalities. With the disincorporation of the ministry of local governments, many duties and responsibilities were distributed especially to the ministry of interior and the other ministries. Until today, the Local Governments General Directorate of the Ministry of Interior have many duties, powers and responsibilities regarding local governments. With the provision of "special management regime can be adopted for major settlements" of the constitution of 1982, establishment of the metropolitan municipalities to solve the big city's problems was taken under constitution guarantee. Function and importance of local governments increased with the metropolitan municipalities which have started to have a place in Turkish Administrative System in the 1984. After this process, The European Charter of Local Self Government was accepted by the Council of European. Turkey accepted some articles of The European Charter of Local Self Government and this process positively affected the local government's conversion. After the interventionist and regulatory role of the state and local governments and supra-national organization to become more functional, functions of local governments have changed both in the international arena and in the case of Turkey. Within the scope of these changes, the special provincial administration which was under the custody of governor was important until 2004, but after this period, the importance and functionality of metropolitan municipalities have increased. Metropolitan Municipality Law No. 5216, Municipality Law No. 5393, Special Provincial Administration Law No. 5302 were put into force in 2004 and 2005 and, these laws brought stronger and more democratic local governments than before in the scope of the conversion of the local governments. In this process, many changes were done in these laws and the system based on the metropolitan municipaity model has been developed. It can be inferred that the need for the Ministry of Local Government will increase in the case of taking some possible changes into consideration in terms of development of local government system in further process. Some major changes are these; establishment of new metropolitan municipalities by uniting certain provinces; inactivating the legal entities of special provincial administrations in these cities; 354 Rüveyda KIZILBOĞA ÖZASLAN – Orhan Veli ALICI Turkish Studies International Periodical For the Languages, Literature and History of Turkish or Turkic Volume 10/1 Winter 2015 closing district governorships which are in district municipalities, but not offering service in an active way. Besides, the Ministry of Interior works as a Ministry of Security and can not meet the demands of local governments. This situation also increases the need for Ministry of Local Government. The fact that the budget of General Directorate of Local governments is only %1,64 within the total budget of Ministry of Interior, also shows that sufficient budget is not provided for local governments by the Ministry of Interior. Considering that relationships between local governments and central government in developed and developing countries are maintained via a ministry unique for local governments, it is seen that establishment of Ministry of Local Government in Turkey became a must. Thus, more autonomous and democratic local government system will be constituted through the Ministry of Local Governments. Generally in this study, the period before the Ministry of Local Administration, the Ministry of Local Government Period (1978-1979), and post-period of ministry of local government is examined. Causes of occurence, organizational structure, duties and the reason for closing of the Ministry are explained and on the other hand, the other implementations of ministries of local governments in other countries are assessed. Within the concept of other countries, Norway, United Kingdom, Ireland, New Zealand, Turkish Republic of Northern Cyprus, Kosovo and Uganda, Zambia and Palestine’s ministry of local governments are taken as a sample and examined. Also, the matters forming a base for the establishment of the Ministry of Local Government in Turkey are examined in the study. Besides, establishment of the Ministry of the Local Governments which will associate the increasing importance of the local governments with the central government and will give the necessary importance to the local governments is questioned.
THE EXPERIENCE OF MINISTRY OF LOCAL GOVERNMENT IN TURKEY AND QUESTIONING OF THE NECESSITY AT THE PRESENT TIME